Apresiasi Masyarakat Miskin Terhadap Layanan Sosial Dasar Pemerintah - Sholichah, Nihayatus (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
Changes in the role of local government as stipulated in Law No. 23/2014 on Local Government, demanding the role of public services for quality local government to the community. In addition, the demand for public services as the rights of citizens who have direct access to the Government brings impacts on climate change in the Local Government, especially as a state servant and community service. Especially when associated with one of the factors that affect the success of an organization, which is oriented to the public service, namely its success in performing the service function to the public (public service) either in the form of goods or services in accordance with the desired needs. The phenomenon that occurs in the fishing community shows that, the level of welfare of life is low. Difficulties in overcoming the problems of daily living and poverty have made people in fishing villages have to bear the burden of life that can not be ascertained when the end. As a result of poverty, there is a difficulty in accessing services in the field of basic social services from the Government which includes food, education and health. Keywords: People's Appreciation, Poverty, Government